Android Smartphone Application to Control Home Lights Based on ESP8266 and IoT - Rendyansyah, Rendyansyah; Yoggi Rahmawan (Universitas Muhammadiyah Surakarta, 2024)
A house often lived in due to someone going to work all day or even on holiday outside the city. There must be a special strategy to activate the lights at night and deactivate the lights during the day. A smart device that can help as a position to turn on and turn off the house lights. Home lights can be controlled remotely using an Android smartphone and IoT internet network. The system is designed on a prototype scale; there are four AC-powered lamps, namely two lamps, each installed inside and outside the house. The ESP8266 microcontroller is a data processing medium for communication from Android smartphones to lighting devices. Utilizing the IoT system to connect the smartphone to the Internet and the ESP8266 forms a system that can be accessed remotely. The Android application on the smartphone has four buttons, namely from light-1 to light-4. All lights can turn on and off on command. When testing a system connected to Firebase, the system can respond well and from a long distance while connected to the Internet. The system response in turning the lights on and off is ±4 seconds, and the longest distance is ±10 km. All control buttons in this system application can function properly according to their function to control home lights by sending data in the form of logic high or logic low to Firebase. This Android-based home light control uses the Internet network, making it easier to turn on or off the house lights while connected to the Internet network.